A Study on Climate Resilient Rice Varieties on Productivity Enhancement under Direct Sown Rainfed Ecosystem - Arunachalam, P.; Ragavan, T. (Journal of Agricultural Extension Management, 2022)
The Ramanathapuram district farmers are practicing North East Monsoon rain dependent semi-dry rice cultivation. The climatic vulnerability of pre-monsoon and intermittent dry spells are major constrains in crop husbandry practices and to harvest remunerative grain yield in semi-dry rice. The Krishi Vigyan Kendra, Ramanathapuram had demonstrated five climate adapted rice varieties to 82 farmers at an area of 31 hectare. The short duration rice varieties namely CO 53, ADT 53 and CO 51 matured in 110 days with grain yield advantage of 35, 20 and 16 percent respectively than conventional variety. If there is no terminal drought or the tank-fed rain water availability is not limited the mid-early rice varieties namely TKM 13 and RNR 15048 gives an average grain yield of 5755 and 5371 kg/ha respectively. Apart from adopting suitable rice varieties, the other main reasons for enhanced grain yield is use of certified seeds ensured good population stand under pre-monsoon dry seeding and nutrient management practices. The extension gap in rice varieties studied ranged from 690 to 1585 kg/ha and technology gap is from 825 to 1179 kg/ha. The benefit cost ratio (BCR) in conventional varieties was 1.72, and in improved rice varieties ranged from 2.01 (CO 51) to 2.25 (TKM 13). Hence concerted extension efforts are needed to ensure adoption of improved technologies on wider scale. The technology index showed Co 53, ADT 53 and TKM 13 has more feasibility to adapt varied soil and climatic variability of this region